Delayed rebleeding of an Acom aneurysm treated with a web device: Endovascular management. Issue 6 (December 2021) - Mine, Benjamin; Bonnet, Thomas; Guenego, Adrien; Elens, Stéphanie; Suarez, Juan V; Lubicz, Boris
We report a case of cerebral aneurysm rerupture 24 months after initial bleeding and complete occlusion using a WEB device. A middle-aged patient was transferred at our institution because of a recurrent aneurysmal bleeding. The patient was graded WFNS2 and unenhanced CT showed a modified Fisher grade 3 SAH. DSA showed an increased compaction and an evolutive "proximal recess" of the WEB device associated with a small unprotected part of the aneurysm wall and a bleb pointing towards the haemorrhage. Balloon- and stent-assisted coiling was performed, allowing to completely occlude the recurrence. The patient suffered no neurological deficit neither delayed complication and was discharged at day 16.